Practicing Responsiveness: Using Approximations of Teaching to Develop Teachers' Responsiveness to Students' Ideas. (January 2020) - Kavanagh, Sarah Schneider; Metz, Mike; Hauser, Mary; Fogo, Brad; Taylor, Megan Westwood; Carlson, Janet
As practice-based teacher education (PBTE) has become more prevalent, debates about its contribution have emerged. Critics of PBTE question whether emphasizing practice will support a technocratic approach to teacher education rather than promoting instruction that is responsive to students' ideas. This qualitative case study was motivated by an interest in understanding whether and in what ways practice-based approaches to teacher learning can support teachers in practicing responsiveness as opposed to practicing decontextualized moves. To this end, we investigated how early-career teachers in a practice-based professional development program were supported to approximate teaching practices. We focused on the extent to which approximations of practice supported teachers to hone their skill at being responsive to students' ideas. Findings revealed characteristics of approximations of practice that support teachers in developing their capacity to enact responsive instruction. These findings have implications for program design, teacher educator pedagogy, and future research.